Over a million students use our free study notes to help them with their homework
Implicit differentiation is used when the function you need to differentiate is not in the form y = f(x). For example: y4 + 3x2 - 10 + 2y2 = 4xThe first step is to differe...
First expand the bracket (x-3)2 separately to give x2 - 6x +9 Next multiply by the 4 outside the brackets to give 4x2 -24x +36 Now all the terms have been expanded you can...
3x + 2y = 12 (2) multiply by 4 (To make the x coefficients equal for both equations)12x + 8y = 48 (3)(3) - (1) 12y = 36Divide through by 12y = 3Sub y = 3 into eq...
Factorising the left hand side we get x2 + x - 6 = (x + 5)(x - 4). Therefore x2 + x - 6 = 0 is the same as (x + 5)(x - 4) = 0. If multiplying two quantities equals 0, this means that...
←
455
456
457
458
459
→
Internet Safety
Payment Security
Cyber
Essentials